2012
DOI: 10.1590/s0100-06832012000300026
|View full text |Cite
|
Sign up to set email alerts
|

Soil, water and nutrient losses by interrill erosion from green cane cultivation

Abstract: Interrill erosion occurs by the particle breakdown caused by raindrop impact, by particle transport in surface runoff, by dragging and suspension of particles disaggregated from the soil surface, thus removing organic matter and nutrients that are essential for agricultural production. Crop residues on the soil surface modify the characteristics of the runoff generated by rainfall and the consequent particle breakdown and sediment transport resulting from erosion. The objective of this study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
(13 reference statements)
0
21
3
8
Order By: Relevance
“…When 50% of straws were kept on the soil surface, the Di was reduced by 91.4% when compared to the value obtained for bare soil. These results are superior to those observed by SILVA et al (2012) to interrill erosion in Oxisol similar to this research that reported 85% of Di reduction in this condition. These differences are probably due to the erodibility of the soil and straw amount applied per plot.…”
Section: Interrill Erosioncontrasting
confidence: 55%
See 4 more Smart Citations
“…When 50% of straws were kept on the soil surface, the Di was reduced by 91.4% when compared to the value obtained for bare soil. These results are superior to those observed by SILVA et al (2012) to interrill erosion in Oxisol similar to this research that reported 85% of Di reduction in this condition. These differences are probably due to the erodibility of the soil and straw amount applied per plot.…”
Section: Interrill Erosioncontrasting
confidence: 55%
“…Such coverage, however, does not guarantee the absence of sediment enriched with clay and/or other nutrients at levels capable of conducting an ER ≤ 1. Furthermore, they are lower than the ones determined by SILVA et al (2012) in Oxisol similar to this research, which evaluate for ER ≤ 1, in case of P has the need of a SC ≥ 25%. These differences are probably due to higher ER rates obtained by SILVA et al (2012), 2.1 for SC of 0% and 0.5% for SC of 100%, regarding the ones of this research of 1.3 for SC of 0% and 0.4 for SC of 100%.…”
Section: Losses Of Clay Available and Adsorbed Phosphorus In The Sedcontrasting
confidence: 44%
See 3 more Smart Citations